Exploring the Feminization of Backseat Gaming Through Girlfriend Reviews YouTube Channel. Issue 5 (July 2022) - Yodovich, Neta; Kim, Jinju
This paper scrutinizes the feminization of backseat gaming by examining the successful YouTube gaming reviews channel, Girlfriend Reviews . As video games are considered a male-dominated hobby, this channel, which provides the perspective of a male gamer's girlfriend offers a compelling case study to explore the ways in which women can access the gaming community. Through analyzing the opinions and sentiments expressed in the comment sections, we explore how viewers engage with the channel and why they support or condone it. We argue that viewers gravitate toward the channel for three significant reasons: the girlfriend being (1) a supportive backseat gamer, (2) who holds no prior knowledge on gaming, and (3) does not engage with feminist discourse. We argue that the position of "the girlfriend"/"backseat gamer" provides women an alternative pathway into the gaming community. However, moments of pushback demonstrate the fragility of women's position in such presumed male-dominated communities.